A Case Report on Cholestatic Jaundice Secondary to Adverse Effect of Phaleria macrocarpa (Mahkota Dewa) - Muhammad Firdaus Abdul Rahim; Alvin Oliver Payus (Acta Medica Indonesiana)
Drug induced cholestatic liver injury can posed a great diagnostic difficulty as a result of its long non-exhaustive list of potential offending causes which can be either prescribed or over-the-counter medications, such as medicinal herbs and remedies. Phaleria macrocarpa, or more commonly known as the ‘God’s crown’ by the local people of South East Asia, is not listed as one of the causes. This medicinal plant extract has been increasingly used for traditional treatment for various ailments. Here, we report a case of a young man who has no known medical illness presented with cholestatic pattern of liver injury which caused by chronic ingestion of Phaleria macrocarpa. The objective of this case report is to share the uncommon side effect of taking this traditional product which may have been under-reported due to the unknown effect.